Biomimetic nanochannels for the discrimination of sialylated glycans via a tug-of-war between glycan binding and polymer shrinkage. Issue 3 (3rd December 2019) - Li, Minmin; Xiong, Yuting; Wang, Dongdong; Liu, Yunhai; Na, Bing; Qin, Haijuan; Liu, Jinxuan; Liang, Xinmiao; Qing, Guangyan
Abstract : A glycan-responsive polymer-modified nanochannels system enables the precise discrimination of sialylated glycan linkage isomers via the different "OFF–ON" changes resulting from a "tug-of-war" between polymer-glycan binding and polymer shrinkage. Abstract : Sialylated glycans that are attached to cell surface mediate diverse cellular processes such as immune responses, pathogen binding, and cancer progression. Precise determination of sialylated glycans, particularly their linkage isomers that can trigger distinct biological events and are indicative of different cancer types, remains a challenge, due to their complicated composition and limited structural differences. Here, we present a biomimetic nanochannels system integrated with the responsive polymer polyethyleneimine- g -glucopyranoside (Glc-PEI) to solve this problem. By using a dramatic "OFF–ON" change in ion flux, the nanochannels system achieves specific recognition for N -acetylneuraminic acid (Neu5Ac, the predominant form of sialic acid) from various monosaccharides and sialic acid species. Importantly, different "OFF–ON" ratios of the conical nanochannels system allows the precise and sensitive discrimination of sialylated glycan linkage isomers, α2–3 and α2–6 linkage (the corresponding ion conductance increase ratios are 96.2% and 264%, respectively). Analyses revealed an unusual tug-of-war mechanism between polymer-glycan binding and polymer shrinkage. The low binding affinity of Glc-PEI for the α2–6-linked glycan caused considerable shrinkage of Glc-PEI layer, but the high affinity for the α2–3-linked glycan resulted in only a slight shrinkage. This competition mechanism provides a simple and versatile materials design principle for recognition or sensing systems that involve negatively charged target biomolecules. Furthermore, this work broadens the application of nanochannel systems in bioanalysis and biosensing, and opens a new route to glycan analysis that could help to uncover the mysterious and wonderful glycoworld.